The Effect of the Talking Stick Method on the Scientific Debate Skills of 10th Grade Students at Sirenja State High School 2 - Oktaviani; Ida Nur’aeni; Sukma; Ulfah; Juniati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to determine the effect of the talking stick method on the scientific debate skills of 10th-grade students at Sirenja State High School 2. The type of research used is quantitative research. The method employed in this study is the quantitative correlation method. The data collection techniques used in this study are: observation, testing, and documentation. The data analysis techniques in this study are the normality test, homogeneity test, and correlation test. The results of teacher observations indicate that the talking stick method achieved a success rate of 85.71%. Observations of student activities also showed high results, with classical learning mastery reaching 91.67%. Validity tests for all instruments indicated validity, and the reliability of the instruments fell into the “moderately reliable” category (α = 0.606). The results of the normality test showed a significance value of 0.036 at a significance level (α) of 0.05, indicating a normal distribution, while the homogeneity test showed a significance value of 0.213, indicating homogeneous variance, meaning the data met the requirements for analysis. Based on the Pearson correlation test, a value of r = 0.365 was obtained with a significance of 0.000 < 0.05, indicating a significant and positive relationship between the talking stick method and students’ scientific debate skills, although the relationship falls into the moderate category. Thus, it can be concluded that the talking stick method significantly influences students’ scientific debate skills, particularly in the aspects of speaking confidence, argument accuracy, and teamwork ability. This study recommends the use of the talking stick method as an alternative learning strategy to enhance students’ critical thinking skills in scientific debate activities.